Pengaruh Metode Tartil Dalam Meningkatkan Kemampuan Membaca Al-Qur’an Sesuai Kaidah Tajwid di Ponpes Talimul Qur’an Tsani - Hayatun Nupus, Syifa; Mulyadi Qosim, Ahmad; Triwoelandari, Retno (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
The Tartil method is a method in which to read the Al-Qur'an directly (without spelling) and practice the habit of reading tartil when reading the Al-Qur'an. In the ability to read the Koran it is important for Muslims to know about the laws of tajwid science such as makhrorijul letters. The purpose of this study was to find out the differences between the control class that did not use the tartil method and the experimental class that used the tartil method. This study uses a quantitative research with an experimental design model and the Pretest-Posttest Control Group Design, in this design there are two groups selected randomly.The results of the study showed an increase in students' Al-Qur'an reading ability in the control class which was taught by not using the tartile method by obtaining a difference between the pre-test and post-test results of 11.88. There is an increase in the ability to read the Qur'an in the experimental class taught using the Tartil method with a difference between the pre-test and post-test results of 18.45. There is a significant difference in the increase in Al-Qur'an reading ability in Islamic boarding schools Ta'limul Qur'an Tsani which is taught not using the tartile method and which is taught using the tartile